Comparative evaluation and influence of new Optibond eXTRa self-etch Universal adhesive and conventional Transbond XT on shear bond strength of orthodontic brackets-An in vitro study - Bhogi Siddarth; Kaladhar Reddy Aileni; Madhukar Reddy Rachala; Arun Kumar Dasari; Jaya Priyanka Mallepally; Pooja Reddy Thadisina; Shaik Navab (Wolters Kluwer Medknow Publications, 2022)
INTRODUCTION: The demand by dental practitioners for adhesives led to the innovation of newer self-etched universal adhesive systems. The objectives were to evaluate the shear bond strength (SBS) of metal brackets bonded with Optibond eXTRa Universal self-etch adhesive and Transbond XT primer and also to assess the adhesive remnant index (ARI). MATERIALS AND METHODS: A total of 100 extracted human premolar tooth samples were divided into 2 groups (n = 50) according to the adhesive system employed: Transbond XT (3M Unitek) and Optibond eXTRa Universal (KaVo Kerr). In group A, Transbond XT primer was applied, and in group B, Optibond eXTRa was applied, and metal brackets (American Orthodontics) were bonded with the Transbond XT adhesive, followed by photopolymerization with LEDition. The samples were preserved in artificial saliva for 30 days. SBS was tested using a universal testing machine (DAK Series7200, India). The ARI was assessed at 10× magnification under a stereomicroscope (Meiji Techno, Japan). The SBS scores were subjected to independent sample t-test and ARI scores to Pearson's Chi-square test. RESULTS: The mean SBS and standard deviation of Transbond XT is 12.11 ± 2.6 MPa and that of Optibond eXTRa Universal is 11.36 ± 2.8 MPa, revealing a statistically nonsignificant difference. Transbond XT displayed higher ARI scores and was statistically significant (P = 0.001). CONCLUSION: The Optibond eXTRa Universal adhesive appears to be preferable for orthodontic bonding as it exhibited clinically acceptable SBS and performed better in terms of the ARI.